Dopamine Transporter (DaT) Scan Utilization in a Movement Disorder Center. Issue 1 (28th October 2015) - Oravivattanakul, Srivadee; Benchaya, Lucas; Wu, Guiyun; Ahmed, Anwar; Itin, Ilia; Cooper, Scott; Gostkowski, Michal; Rudolph, Joseph; Appleby, Kristin; Sweeney, Patrick; Fernandez, Hubert H.
Abstract: Background: The aim of this work was to describe utilization patterns of dopamine transporter (DaT) scan and its influence on patient management at a single movement disorders center. DaT scan helps differentiate between neurodegenerative from non‐neurodegenerative parkinsonism and essential tremor (ET). It has been recently approved in the United States in 2011. Methods: We conducted a retrospective review of all patients, observed by movement disorders neurologists, who received a DaT scan. Demographic data, medication use, and prescan diagnosis were collected. Results: A total of 216 DaT scans were performed at our center from 1 June 2011 to 31 October 2012. A total of 175 scans were included for analysis. Rates of DaT scan utilization varied from 5 to 33 per 100 new patients observed. When our specialists suspected neurodegenerative parkinsonism before the scan (N = 70), the scan was abnormal in 57%. When non‐neurodegenerative parkinsonism was prescan diagnosis (N = 46), the scan was normal in 65%. When essential/dystonic tremor was suspected (N = 14), the scan was normal in 79%. When psychogenic disorder was the prescan diagnosis (N = 15), the scan was normal in only 47%. Only 4% of patients with abnormal scan remained off anti‐PD medications, whereas 24% of patients with negative scan were still on anti‐PD medications. Conclusions: DaT scan utilization among specialists varied greatly. Scan results correlated most when prescan diagnosis was ET than when working diagnosis was neurodegenerative parkinsonism or other non‐neurodegenerative parkinsonism. Scan result was least consistent when prescan diagnosis was psychogenic disorder. Finally, DaT scans influenced medical treatment more when it was abnormal, compared to when it was normal.